The Use of Interactive Multimedia on Religious Tolerance Materials Learning for Students of MAN 1 in Bone Regency - Karim, Bisyri Abdul; Halidin, Ali; Zakiah, St. (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
This thesis discusses the interactive multimedia in increasing the religion tolerance material for MAN 1 Bone students. The purpose is to obtain empirical data about the students' understanding after learning comprehension of the MAN 1 Bone District students. The research used a one-group pre-test and post-test design methodology, which means the experimental research is only one experimental group. The results of this study were: The first is the motivation of students before being treated in the form of interactive multimedia application was in the high category, namely 71.11% based on interpretation criteria. The second, after being treated in the form of the application in interactive multimedia increases. The results of the t-test, which shows t count (6.621)> t ultimate (2.05553), and the results of the analysis of each indicator are 89.99%. So that the proposed hypothesis is accepted. This shows a significant relationship between the application of interactive multimedia in learning religion and tolerance materials in the students' learning at MAN 1 Bone.